Multivariate investigation of parameters in the development and improvement of NiFe cells - Gil Posada, Jorge Omar; Hall, Peter J. (Journal of power sources, 2014)
In this article, we use a surface response approach to investigate the effect of bismuth sulphide as well as the compositions of PTFE in the overall columbic efficiency of a NiFe cell battery. Our results demonstrate that while bismuth sulphide favours the process of charge/discharge of a NiFe cell, the use of metallic bismuth only marginally influences coulombic efficiency. In addition we had found that the presence of the soluble bisulfide anion is not sufficient to increase coulombic efficiency in NiFe cells.